MAINTAINING HERITAGE, EMBRACING CHANGE: ULAMA IN MADURA'S SALAFIYAH PESANTREN - Rohanda, Rohanda; Burhanudin, Dede; Yunani, Ahmad; Saefullah, Asep (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This research examines the role of ulama in education in three salafiyah Islamic boarding schools in Madura: Al-Is'af, Assadad, and Al-Usymuni. The main objective of this research is to analyze the works of ulama that are still used as the main literature in these pesantrens and to investigate how salafiyah pesantrens maintain the quality of traditional religious education while adopting the modern classical education system. The methodology used includes exploration to identify and inventory the works of scholars, as well as content analysis to reveal important information such as author, field of study, and book title. The study found that although salafiyah pesantren have incorporated non-yellow literature into their curriculum, they still maintain a focus on deep religious understanding (tafaqquh fiddin) through the teaching of classical books. The works of ulama are still the main reference in pesantren education, proving the important role of ulama in maintaining the Islamic scientific tradition in Indonesia.